Development of an individual fitness score (IFS) based on the depression treatment guidelines of in the Japanese Society of Mood Disorders. Issue 1 (16th November 2022) - Fukumoto, Kentaro; Kodaka, Fumitoshi; Hasegawa, Naomi; Muraoka, Hiroyuki; Hori, Hikaru; Ichihashi, Kayo; Yasuda, Yuka; Iida, Hitoshi; Ohi, Kazutaka; Ochi, Shinichiro; Ide, Kenta; Hashimoto, Naoki; et al.
Abstract: Aim: Treatment guidelines are designed to assist patients and health care providers and are used as tools for making treatment decisions in clinical situations. The treatment guidelines of the Japanese Society of Mood Disorders establish treatment recommendations for each severity of depression. The individual fitness score (IFS) was developed as a simple and objective indicator to assess whether individual patients are practicing treatment by the recommendations of the depression treatment guidelines of the Japanese Society of Mood Disorders. Methods: The EGUIDE project members determined the IFS through the modified Delphi method. In this article, the IFS was calculated based on the treatment of depressed patients treated and discharged between 2016 and 2020 at facilities participating in the EGUIDE project. In addition, we compared scores at admission and discharge. Results: The study included 428 depressed patients (mild n  = 22, moderate/severe n  = 331, psychotic n  = 75) at 57 facilities. The mean IFS scores by severity were statistically significantly higher at discharge than at admission with moderate/severe depression (mild 36.1 ± 34.2 vs. 41.6 ± 36.9, p  = 0.49; moderate/severe 50.2 ± 33.6 vs. 55.7 ± 32.6, p  = 2.1 × 10–3; psychotic 47.4 ± 32.9 versus 52.9 ± 36.0, p  = 0.23). Conclusion: We developed the IFS based on the depression treatment guideline, which enables us to objectively determine how close the treatment is to the guideline at the time of evaluation in individual cases. Therefore, the IFS may influence guideline‐oriented treatment behavior and lead to the equalization of depression treatment in Japan, including pharmacotherapy.